Analysis of the Molecular Diversity Among Cronobacter Species Isolated From Filth Flies Using Targeted PCR, Pan Genomic DNA Microarray, and Whole Genome Sequencing Analyses - Jang, Hyein; Chase, Hannah R.; Gangiredla, Jayanthi; Grim, Christopher J.; Patel, Isha R.; Kothary, Mahendra H.; Jackson, Scott A.; Mammel, Mark K.; Carter, Laurenda; Negrete, Flavia; Finkelstein, Samantha; Weinstein, Leah; et al. (Frontiers in Microbiology, 2020)
Cronobacter species are opportunistic pathogens capable of causing life-threatening infections in humans, with serious complications arising in neonates, infants, immuno-compromised individuals, and elderly adults. The genus is comprised of seven species: Cronobacter sakazakii, Cronobacter malonaticus, Cronobacter turicensis, Cronobacter muytjensii, Cronobacter dublinensis, Cronobacter universalis, and Cronobacter condimenti. Despite a multiplicity of genomic data for the genus, little is known about likely transmission vectors. Using DNA microarray analysis, in parallel with whole genome sequencing, and targeted PCR analyses, the total gene content of two C. malonaticus, three C. turicensis, and 14 C. sakazaki isolated from various filth flies was assessed. Phylogenetic relatedness among these and other strains obtained during surveillance and outbreak investigations were comparatively assessed. Specifically, microarray analysis (MA) demonstrated its utility to cluster strains according to species-specific and sequence type (ST) phylogenetic relatedness, and that the fly strains clustered among strains obtained from clinical, food and environmental sources from USA, Europe, and Southeast Asia. This combinatorial approach was useful in data mining for virulence factor genes, and phage genes and gene clusters. In addition, results of plasmidotyping were in agreement with the species identity for each strain as determined by species-specific PCR assays, MA, and whole genome sequencing. Microarray and BLAST analyses of Cronobacter fly sequence datasets were corroborative and showed that the presence and absence of virulence factors followed species and ST evolutionary lines even though such genes were orthologous. Additionally, zebrafish infectivity studies showed that these pathotypes were as virulent to zebrafish embryos as other clinical strains. In summary, these findings support a striking phylogeny amongst fly, clinical, and surveillance strains isolated during 2010-2015, suggesting that flies are capable vectors for transmission of virulent Cronobacter spp.; they continue to circulate among USA and European populations, environments, and that this “pattern of circulation” has continued over decades.